Emission-line properties of IllustrisTNG galaxies: from local diagnostic diagrams to high-redshift predictions for JWST - Hirschmann, Michaela; Charlot, Stephane; Feltre, Anna; Curtis-Lake, Emma; Somerville, Rachel S; Chevallard, Jacopo; Choi, Ena; Nelson, Dylan; Morisset, Christophe; Plat, Adele; Vidal-Garcia, Alba (Monthly notices of the Royal Astronomical Society, 2023)
We compute synthetic, rest-frame optical and ultraviolet (UV) emission-line properties of galaxy populations at redshifts from z ≈ 0 to  = 8 in a full cosmological framework. We achieve this by coupling, in post-processing, the cosmological IllustrisTNG simulations with new-generation nebular-emission models, accounting for line emission from young stars, post-asymptotic giant branch (PAGB) stars, accreting black holes (BHs) and, for the first time, fast radiative shocks. The optical emission-line properties of simulated galaxies dominated by different ionizing sources in our models are largely consistent with those expected from classical diagnostic diagrams and reflect the observed increase in [O iii]/Hβ at fixed [N ii]/Hα and the evolution of the Hα, [O iii]λ5007, and [O ii] λ3727 luminosity functions from z ≈ 0 to ∼ 2. At higher redshift, we find that the emission-line galaxy population is dominated by star-forming and active galaxies, with negligible fractions of shock- and PAGB-dominated galaxies. We highlight 10 UV-diagnostic diagrams able to robustly identify the dominant ionizing sources in high-redshift galaxies. We also compute the evolution of several optical- and UV-line-luminosity functions from z = 4 to 7, and the number of galaxies expected to be detectable per field of view in deep, medium-resolution spectroscopic observations with the NIRSpec instrument on board the JWST. We find that 2-h-long exposures are sufficient to achieve unbiased censuses of Hα and [O iii]λ5007 emitters, while at least 5 h are required for Hβ, and even 10 h will detect only progressively smaller fractions of [O ii] λ3727, O iii] λ1663, C iii] λ1908, C iv λ1550, [N ii]λ6584, Si iii] λ1888, and He ii λ1640 emitters, especially in the presence of dust.